Novel cilengitide-based cyclic RGD peptides as alpha nu beta(3) integrin inhibitors - Meena, Chhuttan L.; Singh, Dharmendra; Weinmueller, Michael; Reichart, Florian; Dangi, Abha; Marelli, Udaya Kiran; Zahler, Stefan; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2020)
In this letter, we report a series of five new RGD-containing cyclic peptides as potent inhibitors to alpha nu beta(3) integrin protein. We have incorporated various unnatural lipophilic amino acids into the cyclic RGD framework of cilengitide, which is selective for alpha nu beta(3) integrin. All the newly synthesized cyclic peptides were evaluated in vitro solid phase binding assay and investigated for their binding behaviour towards integrin subtypes. All the cyclic peptides were synthesized in excellent yield following solution-phase coupling strategy. The cyclic RGD peptides 1a-e exhibited IC50 of 9.9, 5.5, 72, 11 and 3.3 nM, respectively, towards a alpha nu beta(3) integrin protein. This finding offers further opportunities for the introduction unusual amino acids into the cyclic peptide framework of cilengitide.
Keywords: Anticancer drugs; Cilengitide; Integrins; RGD cyclicpeptides